2014
DOI: 10.1002/chem.201400218
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Methane Activation by La6O10 Cluster Anions

Abstract: The first example of a metal oxide cluster anion, La6 O10 (-) that can activate methane under ambient conditions is reported. This reaction is facilitated by the oxygen-centered radical (O(-⋅) ) and follows the hydrogen atom transfer mechanism. The La6 O10 (-) has a high vertical electron detachment energy (VDE=4.06 eV) and a high symmetry (C4v ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…Gas‐phase studies of methane activation by metal atoms and clusters have provided insight into methane functionalization at the molecular level . In the case of platinum the reactivities of its cationic, neutral, and anionic atoms and clusters with methane have been widely investigated .…”
Section: Figurementioning
confidence: 99%
“…Gas‐phase studies of methane activation by metal atoms and clusters have provided insight into methane functionalization at the molecular level . In the case of platinum the reactivities of its cationic, neutral, and anionic atoms and clusters with methane have been widely investigated .…”
Section: Figurementioning
confidence: 99%
“…[4,22,23] It was reported that the anions are mostly inert or react very slowly with methane. [4,22,23] It was reported that the anions are mostly inert or react very slowly with methane.…”
mentioning
confidence: 99%
“…Oxide cluster anions are usually inert with methane and it has been only recently identified that La 6 O 10 À and La 8 O 13 À anions can activate CH 4 through the OC À centers to generate CH 3 [Reaction (1)] under thermal collision conditions whereas the reaction efficiencies are quite low (F = 0.02-0.03 %), [22] in sharp contrast to the good efficiency of (7.0 AE 3.5) % for PtAl 2 O 4 À with CH 4 . This also implies that methane activation by PtAl 2 O 4 À follows a different mechanism.…”
mentioning
confidence: 99%
“…178 The two cluster anions can abstract one hydrogen atom from methane to generate CH 3 178 The two cluster anions can abstract one hydrogen atom from methane to generate CH 3…”
Section: Reaction With Organic Substratesmentioning
confidence: 99%